UNIT 14.24 Single‐Molecule mRNA Detection in Live Yeast. Issue 1 (4th January 2016) - Lenstra, Tineke L.; Larson, Daniel R.
Abstract : Visualization of single RNA molecules in living cells has enabled the study of synthesis, movement, and localization of mRNAs and has provided insight into gene regulation with sub‐second temporal resolution and nanometer spatial resolution. Studies of transcription in single cells indicate that gene activity is heterogeneous between cells and exhibits random variability over time, even within single cells. Studies of mRNAs in yeast can take advantage of the powerful genetics available in this model organism and allow mechanistic questions to be addressed. In this unit, we describe an approach for visualizing mRNA and transcription in live yeast cells. The method is based on binding of fluorescently labeled MS2 and PP7 coat proteins to stem loop sequences that are introduced into the gene of interest. Detailed protocols are provided for the construction of the necessary yeast strains, for image acquisition, and for validation. © 2016 by John Wiley & Sons, Inc.